ON THE HISTORY OF EDUCATION DEVELOPMENT AMONG THE NOGAIS OF THE NORTH CAUCASUS (XVII–XX CENTURIES) - Gimbatova, Madina Bagavutdinovna; Zineeva, Zaida Zalimhanovna (History, Archeology and Ethnography of the Caucasus, 2020)
The article is devoted to one of the poorly studied issues in historical science – the formation and development of education among Nogais. The relevance of the study is due to the importance of education as a basic component of the spiritual culture of an ethnic group, the focus of the research outcome on promoting the cultural growth of the modern Nogais, preserving their ethnocultural identity, and strengthening ethnic self-awareness. The methodological and theoretical basis of the study lies in the principle of historicism, as well as historical-comparative and historical-typological methods. Based on the new archival documents and field material, the stages of public education of the Nogais have been identified as follows: pre-revolutionary (pre-Soviet), Soviet and post-Soviet. With the adoption of Islam by the Nogais around 1254–1256, a whole network of maktabs and madrasas emerged in the Nogai steppe, in which students studied the foundations of Islam, Arabic script and literature, works of advanced scientific thought and Oriental literature. After the inclusion of territories with the Nogai population into the Russian Empire, secular schools and colleges were opened, in which, thanks to the influence of progressive Russian culture, Nogai learned the achievements of world culture and joined the all-Russian cultural field. In the XIX century, the Nogai education produced literary men, enlighteners and public figures, who were notable not only in Russia but also in the countries of the Middle East. With the establishment of Soviet rule in the country, illiteracy among the Nogais was eliminated. The emergence of national schools and teachers of the native language served the formation of the Soviet Nogai intelligentsia. Its most important merit was the creation of a new Nogai written language, its modern literary form, educational and reference literature in the Nogai language. In the conclusion, the Nogai public education, having passed certain stages in its formation and development, has reached a new qualitative level that meets the requirements of the Russian educational system.
Keywords: Nogai; education; schools; madrasas; school; muallim; teacher.